Melatonin delays dark-induced leaf senescence by inducing miR171b expression in tomato - Wang, Kaixin; Cai, Shuyu; Xing, Qufan; Qi, Zhenyu; Fotopoulos, Vasileios; Yu, Jingquan; Zhou, Jie (My University, 2022)
Melatonin functions in multiple aspects of plant growth, development, and stress response. Nonetheless, the mechanism of melatonin in plant carbon metabolism remains largely unknown. In this study, we investigated the influence of melatonin on the degradation of starch in tomato leaves. Results showed that exogenous melatonin attenuated carbon starvation-induced chlorophyll degradation and leaf senescence. In addition, melatonin delayed leaf starch degradation and inhibited the transcription of starch-degrading enzymes after sunset. Interestingly, melatonin-alleviated symptoms of leaf senescence and starch degradation were compromised when the first key gene for starch degradation, α-glucan water dikinase (GWD), was overexpressed. Furthermore, exogenous melatonin significantly upregulated the transcript levels of several microRNAs, including miR171b. Crucially, the GWD gene was identified as a target of miR171b, and the overexpression of miR171b ameliorated the carbon starvation-induced degradation of chlorophyll and starch, and inhibited the expression of the GWD gene. Taken together, these results demonstrate that melatonin promotes plant tolerance against carbon starvation by upregulating the expression of miR171b, which can directly inhibit GWD expression in tomato leaves.
Keywords: Carbon starvation; Chlorophyll; Growth; miRNAs; Resistance; Starch degradation; α-glucan water dikinase (GWD)